2014
DOI: 10.1021/jz500949g
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional Sn- and Fe-Codoped In2O3Colloidal Nanocrystals: Plasmonics and Magnetism

Abstract: We prepared Fe- and Sn-codoped colloidal In2O3 nanocrystals (∼6 nm). Sn doping provides free electrons in the conduction band, originating localized surface plasmon resonance (LSPR) and electrical conductivity. The LSPR band can be tuned between 2000 and >3000 nm, depending on the extent and kind of dopant ions. Fe doping, on the other hand, provides unpaired electrons, resulting in weak ferromagnetism at room temperature. Fe doping shifts the LSPR band of 10% Sn-doped In2O3 nanocrystals to a longer wavelength… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
58
0
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 57 publications
(64 citation statements)
references
References 33 publications
(62 reference statements)
4
58
0
2
Order By: Relevance
“…Plasmonic semiconductor oxide nanocrystals such as Al-doped ZnO (AZO), [1][2][3] indium-doped ZnO (IZO), 3,4 Ga-doped ZnO (GZO), 3 Sn-doped In 2 O 3 (ITO), [6][7] Sb-doped SnO 2 (ATO) 8,9 or others [10][11][12][13][14] have attracted growing attention due to their applicability in many optoelectronic applications, such as nearinfrared selective electrochromic devices, 15 (flexible) displays 11 and polymer light emitting diodes. 4 They also demonstrate excellent bio-sensing and chemical sensing capabilities 16 .…”
Section: Introductionmentioning
confidence: 99%
“…Plasmonic semiconductor oxide nanocrystals such as Al-doped ZnO (AZO), [1][2][3] indium-doped ZnO (IZO), 3,4 Ga-doped ZnO (GZO), 3 Sn-doped In 2 O 3 (ITO), [6][7] Sb-doped SnO 2 (ATO) 8,9 or others [10][11][12][13][14] have attracted growing attention due to their applicability in many optoelectronic applications, such as nearinfrared selective electrochromic devices, 15 (flexible) displays 11 and polymer light emitting diodes. 4 They also demonstrate excellent bio-sensing and chemical sensing capabilities 16 .…”
Section: Introductionmentioning
confidence: 99%
“…1 Also, no impurity peak was observed in XRD data of Fe−Sn codoped In 2 O 3 NCs. 1 Another possible reason for reduction of free electron concentration with Fe doping could be that the Sn concentration remains the same producing an equal number of free electrons both in the presence and absence of Fe, but Fe 3+ takes up some of those free electrons converting to Fe 2+ . In fact, prior studies on Fe-doped In 2 O 3 bulk samples have indicated when the sample is treated under reducing conditions, Fe 3+ can get reduced by consuming the electron obtained from oxygen vacancies as suggested by eq 1.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…1 Sn doping provides free electrons for LSPR and Fe doping provides magnetic spin. In this paper, we control the interaction between two kinds of dopants in Fe−Sn codoped In 2 O 3 nanocrystals, via probing the atomic bonding and ion valence of dopant ions.…”
Section: ■ Introductionmentioning
confidence: 99%
“…[49] Thed ensity of these valence band holes can be reversibly controlled by employing areducing or an oxidizing atmosphere,t hereby allowing reversible tuning of the LSPR band. [11,[52][53][54][55] Similar to bulk TCOs in which oxygen vacancies promote ntype doping,t he LSPR from TCO nanocrystals is also dominated by n-type doping.Atypical LSPR band from Sn 4+ -doped In 2 O 3 (ITO) nanocrystals is shown in Figure 6c. [12,51] On the other hand, bulk and thin films of transparent conducting oxides (TCO) exhibit ahigh density of delocalized electrons in the conduction band.…”
Section: Charge Doping By Heterovalent Ions For Plasmonic Propertiesmentioning
confidence: 99%